2011
DOI: 10.1158/0008-5472.can-10-1030
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Assessment of New Mechanism-Based Pharmacodynamic Biomarkers for MLN8054, a Small-Molecule Inhibitor of Aurora A Kinase

Abstract: The mitotic kinase Aurora A is an important therapeutic target for cancer therapy. This study evaluated new mechanism-based pharmacodynamic biomarkers in cancer patients in two phase I studies of MLN8054, a small-molecule inhibitor of Aurora A kinase. Patients with advanced solid tumors received MLN8054 orally for 7 consecutive days in escalating dose cohorts, with skin and tumor biopsies obtained before and after dosing. Skin biopsies were evaluated for increased mitotic cells within the basal epithelium. Tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 30 publications
(46 reference statements)
3
35
0
Order By: Relevance
“…MLN8054 showed sustained growth inhibition in multiple human tumor xenografts, with phenotypes consistent with AAK inhibition, in preclinical studies (25). In clinical studies, similar pharmacodynamic effects were reported, indicating AAK inhibition in skin and tumor tissues (34)(35)(36); however, dose escalation was stopped, and the MLN8054 development program discontinued, based on benzodiazepine-like somnolence and neurocognitive changes (34). Consistent with the expected activity of an AAK inhibitor, treatment with the second-generation agent MLN8237 has been shown to be associated with an accumulation of cells with abnormal mitotic spindles, leading to decreased proliferation and apoptosis in a range of human tumor cell lines (37)(38)(39)(40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…MLN8054 showed sustained growth inhibition in multiple human tumor xenografts, with phenotypes consistent with AAK inhibition, in preclinical studies (25). In clinical studies, similar pharmacodynamic effects were reported, indicating AAK inhibition in skin and tumor tissues (34)(35)(36); however, dose escalation was stopped, and the MLN8054 development program discontinued, based on benzodiazepine-like somnolence and neurocognitive changes (34). Consistent with the expected activity of an AAK inhibitor, treatment with the second-generation agent MLN8237 has been shown to be associated with an accumulation of cells with abnormal mitotic spindles, leading to decreased proliferation and apoptosis in a range of human tumor cell lines (37)(38)(39)(40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 62%
“…Tumor biopsies were collected before dosing on day 1 and 6 to 8 hours postdose on days 1, 7, 14, and 21. Immunolabeling of skin and tumor biopsies for the quantification of mitotic cells and of tumor biopsies for the assessment of chromosome alignment and spindle bipolarity were conducted as previously described (36). For detection of apoptotic cells, 5-mm sections of formalin-fixed, paraffin-embedded skin punch biopsies were deparaffinized and stained by standard methods with hematoxylin and eosin using a Leica Autostainer XL (Meyer Instruments, Inc.).…”
Section: Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of small-molecule aurora kinase inhibitors have recently been developed and intensively investigated both experimentally and in numerous clinical trials in human medicine [16,[21][22][23]. However, there are no published data showing the effect of aurora kinase inhibitors in veterinary medicine at the time of this writing.…”
Section: Discussionmentioning
confidence: 99%
“…ZM447439 does not interfere with the activities of regular cell cycles in normal cells, and does not affect important regulators such as cdc2, cdc25, MAPK (Mitogen-Activated Protein Kinase) or cyclin B [18]. Aurora kinases are now an attractive target in human cancer therapy, and intensive research including preclinical and clinical trials have been reported [19][20][21][22][23]; however, to our knowledge, scant information exists on the efficacy of aurora kinase inhibition in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%